2022
DOI: 10.1097/md.0000000000031780
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal involvement in systemic sclerosis: An updated review

Abstract: The gastrointestinal tract (GI) is the second most affected organ system in individuals suffering from systemic/localized scleroderma (SSc) or localized scleroderma. SSc can affect any part of the GI, between the oral cavity and anorectum. The annual incidence of SSc in the United States is estimated to be 19.3 cases per million adults, with the highest incidence reported in people aged 44 to 55. Females are 5 times more likely than males to suffer from SSc. Morbidity and mortality rates associated with SSc ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…Most GI specialists would start treatment when symptoms develop, but it is known that this kind of dysmotility medication has better responses when the muscle isńt atrophied or fibrotic. Furthermore, dysmotility agents do not affect disease progression [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most GI specialists would start treatment when symptoms develop, but it is known that this kind of dysmotility medication has better responses when the muscle isńt atrophied or fibrotic. Furthermore, dysmotility agents do not affect disease progression [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that fewer years of education, self-reported race or ethnicity other than White, living in Canada or the UK, having a higher BMI, pruritus, pain intensity and mRSS were associated with greater impairment in satisfaction with one’s social functioning. Among those with large associations, gastrointestinal involvement may reduce one’s ability to carry out social roles due to symptoms such as nausea, abdominal pain or faecal incontinence 36 ; pulmonary arterial hypertension can cause breathlessness, fatigue and dizziness, which can impact the ability to perform everyday tasks such as travelling to work or taking care of household chores 37 38 ; hand and joint involvement can decrease one’s the ability to carry out many tasks necessary for work or household roles 8 ; overlap syndromes, including rheumatoid arthritis or Sjogren’s syndrome, present their own challenges and can exacerbate other symptom-related barriers from SSc.…”
Section: Discussionmentioning
confidence: 99%
“…In SSc, dysmotility is one of the main mechanisms responsible for serious GI manifestations such as reflux esophagitis, gastroparesis, small intestinal bacterial overgrowth, or pseudo-obstructions, all of which might be potential leading causes of malnutrition. 18, 21 Beyond severe involvement, various symptoms and associated complications of GI involvement can contribute to the predisposition of malnutrition in SSc patients. In our cohort, SSc patients were found to have a notable frequency of malnutrition risk with 25.6% classified as having moderate (16%) to high (9.6%) risk for malnutrition and %5 patients with underweight.…”
Section: Discussionmentioning
confidence: 99%